Weed That Strings the Hangman's Bag a Flavia de Luce mystery - Bradley, C. Alan (New York : Delacorte Press, 2010)
Flavia de Luce, a dangerously brilliant eleven-year-old with a passion for chemistry and a genius for solving murders, sets out to solve the murder of a beloved puppeteer. All clues point toward a suspicious death years earlier and a case the local constables can't solve--without Flavia's help.
Keywords: Detectives -- England; Murder -- Investigation; England; Mystery fiction